Best Practices for Shoppers at the Farmers’ Market - Maria J. Rometo; Jamie Sapijaszko; Soohyoun Ahn (EDIS, 2017)
This factsheet is one in a “Florida Farmers’ Markets” series that is designed to provide information to managers, vendors and shoppers of Florida farmers’ markets on topics highly relevant to starting and running a food business: regulations, best practices, and marketing.